Manufacturing Biodegradable Bioplastics from A Mixture of Starch and Kapok Fibers with Variations of Chitosan and Glycerol - Rahmatullah Rahmatullah; Rizka Wulandar Putri; Enggal Nurisman; Yandriyani Yandriyani; Alek Al Hadi; Muhammad Anwar Raihan (Universitas Darussalam Gontor, 2024)
Biodegradable bioplastics are the latest solution to the problem of conventional plastics which hurt the environment. Types of biodegradable bioplastics, namely starch-based plastics and cellulose-based plastics, have been developed in many studies. Cellulose can be made into biodegradable bioplastics by adding starch, plasticizers, and strengthening materials with certain variations. This research aims to determine the effect of mixing glycerol plasticizer and the concentration of chitosan on the biodegradable bioplastics produced. The variables observed started from elongation, Young's modulus, density, tensile strength, biodegradability, and water resistance. The best biodegradable bioplastics results for density, tensile strength, and percent elongation values were obtained with variations of 60% glycerol and 3 gram chitosan of 5.62 g / mL, 163.5 KPa and 4.26 KPa; Young's modulus for variations of 20% glycerol and 3-gram chitosan is 45.17 KPa; the water absorption capacity of variations of 20% glycerol and 0.5-gram chitosan is 81.5%; and the bioplastic mass degraded at a variation of 40% glycerol and 3-gram chitosan at 49.21%.